Preparation method and application of silver crystal powder
By using silver sulfate, specific reducing agents and protective agents to prepare silver crystal powder under controlled reaction conditions, the problem of insufficient shrinkage and crystallization performance of existing silver powder is solved, better shrinkage and crystallization performance are achieved, and the reliability and conductivity of electronic components are improved.
Patent Information
- Application Number
- CN202411564074.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The existing silver powder preparation method requires silver powder with better shrinkability and crystallinity in electronic equipment and other components, but the silver powder prepared by the existing method has the problem of insufficient shrinkage and crystallinity.
Silver sulfate is used as the silver source, and the reduction reaction is controlled in the presence of specific reducing agents and protective agents to prepare silver crystal powder with good shrinkage and crystallization properties.
The prepared silver powder has good shrinkage characteristics and crystallization properties, which improves the reliability and stability of electronic components, and forms a conductive network to improve conductivity.
Smart Images

Figure CN119870488A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal particle preparation, and in particular to a preparation method of silver crystal powder and application thereof. Background Art
[0002] Silver powder has good applications in the electronics industry, energy field, anti-corrosion coatings, decoration field, and cosmetics industry due to its good metallic luster, conductivity, and stability. At present, the preparation methods of silver powder include physical and chemical methods. Physical methods include laser ablation, high-energy ball milling, and atomization. Chemical methods include liquid phase reduction, microemulsion, and liquid phase precipitation conversion. Among them, the liquid phase reduction method is simpler and has better effects and is widely used. It is to add a reducing agent to the silver salt solution, and reduce the silver ions to silver elements by controlling the conditions of the reduction reaction. In order to prepare ultrafine silver powder, a certain dispersant or protective agent is often added to the reduction system to reduce the agglomeration of silver particles.
[0003] Patent JP2000129318A (failed) silver powder and its production discloses mixing an aqueous reaction system containing a silver salt with an aqueous solution containing a reducing agent to reduce and precipitate silver particles to obtain silver powder.
[0004] Patent JP2006063414A (expired) contains silver powder with spherical high-roughness silver particles, silver powder with flaky high-roughness silver particles, a mixed powder of the above two silver powders, a method for making these silver powders, silver ink and silver paste containing these silver powders, and a method for making these silver powders. The silver powders are prepared by using silver nitrate, a complexing agent and a reducing agent.
[0005] Patent JP2007239077A (Effective) A method for producing fine silver particles and fine silver particles obtained by the method discloses mixing a silver salt solution containing a silver salt, a chelating agent and gelatin with a reducing agent solution containing a reducing agent to produce fine silver particles.
[0006] Patent JP2009120940A (failed) The method for producing metal nanoparticles discloses that silver particles are prepared using a silver precursor and a non-polar solution.
[0007] Since silver nitrate has better solubility and reactivity, it can be better adapted to the chemical reduction process of silver powder, and can better control the particle size and morphology of silver powder, so the above patents all use silver nitrate as the silver source for preparing silver powder. However, although the silver powder prepared by the above method has certain advantages in some aspects, electronic equipment and other components also need silver powder with better shrinkage and crystallinity, and the silver powder prepared by the above method also has the problem of insufficient shrinkage and crystallinity. The purpose of the present invention is to provide a new method for preparing silver powder. Summary of the invention
[0008] The present invention aims to provide a novel method for preparing silver powder, which uses silver sulfate as a silver source, adds a specific reducing agent and a protective agent, and controls the reaction conditions. The silver powder finally prepared has good shrinkage and crystallization properties and good application prospects. The specific technical scheme of the present invention is:
[0009] In a first aspect, the present invention provides a method for preparing silver crystal powder, the method comprising:
[0010] Silver sulfate and a reducing agent are added to the acidic solution of the protective agent, and a reduction reaction is carried out under heating and stirring conditions to obtain silver crystal powder.
[0011] In any embodiment, the protective agent is at least one of gum arabic, propyl cellulose, ethyl cellulose, and polyvinyl pyrrolidone;
[0012] Preferably, the protective agent is gum arabic.
[0013] In any embodiment, the reducing agent is selected from at least one of ascorbic acid, hydrazine, hydroquinone, phenylhydrazine and formalin;
[0014] Preferably, the reducing agent is ascorbic acid.
[0015] In any embodiment, the heating temperature is 30-80° C. and the reaction time is 5-1 h.
[0016] In any embodiment, silver sulfate is added in the form of a silver sulfate dispersion, and the concentration of the added silver sulfate dispersion is 0.01 mol / dm 3 -1mol / dm 3 ;
[0017] In any embodiment, the concentration of the protective agent in the acidic solution of the protective agent is 1 g / L-20 g / L;
[0018] In any embodiment, the mass ratio of the added silver sulfate to the protective agent (0.01-0.2): 1;
[0019] In any embodiment, the molar ratio of the reducing agent to silver sulfate is 0.5-2.
[0020] In any embodiment, the solvent of the acidic solution and the solvent of the silver sulfate dispersion are both selected from water or an organic solvent.
[0021] In any embodiment, the pH of the acidic solution is below 2;
[0022] In any embodiment, the pH of the solution is adjusted to below 2 by adding sulfuric acid.
[0023] In any embodiment, the organic solvent does not contain a hydroxyl group; the organic solvent does not contain a hydroxyl group includes but is not limited to acetone.
[0024] In a second aspect, the present invention provides a silver crystal powder, wherein the silver crystals in the silver crystal powder have an intensity ratio I in the (111) and (200) directions. (111) / I (200) Greater than 4.
[0025] In a third aspect, the present invention provides a silver paste comprising silver crystal powder prepared by the method of the first aspect.
[0026] In any embodiment, the silver paste has a porous structure after sintering.
[0027] In a fourth aspect, the present invention provides a method for preparing a silver paste, comprising:
[0028] Ethyl cellulose, butyl carbitol acetate, and the silver crystal powder prepared by the method of the first aspect or the silver crystal powder provided by the second aspect are mixed, and the viscosity is adjusted to obtain a silver paste.
[0029] In any embodiment, the mass proportions of the silver crystal powder, ethyl cellulose and butyl carbitol acetate in the silver paste are 70-90wt%, 1-10wt% and 9-20wt%, respectively.
[0030] In a fifth aspect, the present invention provides a method of applying the silver paste provided in the third aspect or the fourth aspect to an electrode surface.
[0031] The method of applying the silver paste of the present invention to the electrode surface includes but is not limited to coating the silver paste on the electrode surface and then curing it, which can improve the reliability of the corresponding electronic components.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The present invention uses silver sulfate instead of the traditional silver nitrate. Since the solubility of silver sulfate is relatively low and the stability in the solution is high, the release rate of silver ions can be better controlled, and the reaction speed and the size and morphology of the generated silver particles can be more easily controlled, so that the prepared silver particles are more uniform.
[0034] 2. The silver crystal powder provided by the method of the present invention has good shrinkage characteristics, which can achieve tight packaging, thereby helping to improve the reliability and stability of electronic components prepared using the silver crystal powder, and the good shrinkage performance is also conducive to forming a conductive network and improving conductivity;
[0035] 3. The silver crystal powder (111) provided by the method of the present invention has a high orientation, which can reduce scattering and obstruction and form a conductive network, which is more conducive to the transmission of electrons in the crystal, thereby improving the conductivity of the silver powder;
[0036] 4. The silver paste provided by the present invention uses silver crystal powder with high (111) orientation and has a porous structure. These porous structures make the silver paste have good flexibility, stress resistance and heat dissipation performance; in addition, the porous structure makes a large number of pores inside it, and these pores can provide a certain buffer space when the material is subjected to external force or thermal stress, so that the silver paste can better adapt to the stress changes caused by factors such as differences in thermal expansion coefficients between different components, avoid cracks, fractures and other problems, thereby improving the reliability and durability of the packaging connection; in addition, the high specific surface area brought by the porous structure can enhance the adhesion of the silver paste to the substrate;
[0037] 5. The preparation method of the present invention uses low-temperature sintering, the method is simple, and the energy consumption and cost are low. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a reaction concept diagram of the present invention;
[0039] Figure 2 is a SEM image of the silver crystal powder synthesized in Example 1;
[0040] Figure 3 is a particle size distribution diagram of the silver crystal powder synthesized in Example 1;
[0041] Figure 4 is a graph showing the relationship between the concentration of gum arabic added in the present invention and the silver powder D50;
[0042] Figure 5 is the X-ray diffraction pattern of silver crystal powder in Example 1 and Comparative Example 1;
[0043] Figure 6 is the differential thermogravimetric curve of the silver crystal powder in Example 1 and Comparative Example 1;
[0044] Figure 7 is the shrinkage curve of the silver paste prepared from the silver powder in Example 4 and Comparative Example 2;
[0045] Figure 8 is the relationship between the sintering temperature and resistivity of the silver paste prepared from the silver powder in Example 4;
[0046] Fig. 9 It is the SEM picture of the structure of the silver paste sintered body prepared by the silver powder in Example 4 and Comparative Example 2. DETAILED DESCRIPTION
[0047] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0048] The present application embodiment provides a method for preparing silver crystal powder, which comprises:
[0049] Silver sulfate and a reducing agent are added to an acidic solution of a protective agent, and a reduction reaction is carried out under heating and stirring conditions to obtain silver crystal powder, which can solve the problem that the silver powder prepared by the existing method also has insufficient shrinkage performance and crystallization performance.
[0050] The present invention uses silver sulfate instead of the traditional silver nitrate, because the solubility of silver sulfate is relatively low and the stability in the solution is high, the release rate of silver ions can be better controlled, and the reaction speed and the size and morphology of the generated silver particles can be more easily controlled, so that the prepared silver particles are more uniform.
[0051] In any embodiment, the protective agent is at least one of gum arabic, propyl cellulose, ethyl cellulose, and polyvinyl pyrrolidone;
[0052] The protective agent of the present invention is adsorbed on the surface of the generated silver particles, which is beneficial to preventing the silver particles from agglomerating and controlling the growth of the silver particles, and ultimately affecting the morphology, particle size and performance of the silver powder;
[0053] Preferably, the protective agent is gum arabic;
[0054] Gum arabic has good dispersibility and can effectively disperse silver particles in the solution to prevent particle aggregation and precipitation. This helps to control the size of silver particles and improve the uniformity and stability of silver powder, ensuring product quality. In addition, gum arabic exhibits stable chemical properties in acidic solutions and is not prone to decomposition or deterioration, which helps to maintain the stability of the reaction system, reduce the occurrence of side reactions, and improve the purity and yield of the product. In addition, compared with some other chemically synthesized protective agents, gum arabic has less impact on the environment and is safer. Using gum arabic as a protective agent can also improve the tap density and monodispersity of silver powder.
[0055] As an example, when the protective agent of the present invention is selected as gum arabic, the concentration ratio of the reducing agent (R) and the silver sulfate (M) is maintained at a certain ratio, the particle size change of the prepared silver crystal powder is as follows: Figure 4 .Depend on Figure 4It can be seen that if R / M=1, increasing the concentration of gum arabic will change D50 from 1,300 nm to 500 nm, indicating that the concentration of gum arabic has a significant effect on the particle size of the prepared silver crystal powder.
[0056] In any embodiment, the reducing agent is selected from at least one of ascorbic acid, hydrazine, hydroquinone, phenylhydrazine and formalin;
[0057] Preferably, the reducing agent is ascorbic acid; the reducing property of ascorbic acid is suitable, which helps to better control the reaction rate and the quality of the product during the preparation process. In addition, when ascorbic acid is used as a reducing agent, the reaction process is relatively easy to control, which is conducive to the production of silver powder particles with uniform particle size distribution and regular shape; ascorbic acid has less impact on the environment and brings lower health risks to operators.
[0058] In any embodiment, the heating temperature is 30-80°C and the reaction time is 1-5h;
[0059] The reaction process of the present invention adopts low-temperature sintering. During the low-temperature sintering process, the organic components in the porous silver paste are more easily volatilized and decomposed, so that the silver particles can be better connected and fused to each other to form a dense conductive structure. The lower sintering temperature can reduce the thermal damage to sensitive components such as chips, reduce the energy consumption in the packaging process, and is conducive to large-scale production and automated production.
[0060] In any embodiment, the stirring is performed using a stirrer. Here, the type of stirrer is not limited, but examples thereof include: a magnetic stirrer or a stirrer with blades. The intensity of the stirring is also not limited, and the stirring intensity is sufficient to ensure that the solution is fully mixed without being scattered from the container.
[0061] In any embodiment, the molar ratio of the reducing agent to silver sulfate is 0.5-2;
[0062] The reducing agent of the present invention reduces silver ions to metallic silver, and the amount of the reducing agent affects the speed and efficiency of the reduction reaction, thereby affecting the purity and yield of the silver powder; if the amount of the reducing agent is too large, the particle size distribution of the silver powder will become wider, affecting its uniformity and consistency, and may also trigger side reactions, produce unnecessary impurities or by-products, and these impurities may reduce the purity and conductivity of the silver powder; insufficient reducing agent will lead to incomplete reaction, thereby reducing the yield and yield of the silver powder, and due to insufficient reaction, the generated silver particles may have irregular shapes and larger particle sizes, affecting the physical and chemical properties of the silver powder. However, according to the reaction volume or the concentration of silver sulfate, when the size of the reaction container and the concentration of silver sulfate are appropriate, the molar ratio can also be less than 0.5 or more than 2.0.
[0063] In any embodiment, the concentration of the added silver sulfate dispersion is 0.01 to 1 mol / dm 3 ;
[0064] The silver sulfate of the present invention is used as the source of silver ions. The amount of silver sulfate added affects the concentration of silver ions in the reaction system. The concentration of the added silver sulfate in the dispersion is controlled to be 0.01-1 mol / dm 3 , can ensure the smooth progress of the reaction, while greater than or less than this value may affect the yield and purity of the silver powder.
[0065] In any embodiment, the concentration of the added protective agent is 1 g / L to 20 g / L;
[0066] In any embodiment, the mass ratio of silver sulfate added to the protective agent is (0.01-0.2):1.
[0067] The protective agent of the present invention plays the role of stabilizing silver particles and preventing agglomeration in the reaction. By controlling the concentration and the amount of the protective agent added, the particle size and morphology of the silver powder can be effectively controlled, thereby improving the dispersibility and stability of the silver powder.
[0068] In any embodiment, the organic solvent does not contain a hydroxyl group, which is not specifically limited, and an example is given such as acetone;
[0069] The present invention does not use a hydroxyl-containing organic solvent because a solvent having a hydroxyl group will hydrolyze sulfate.
[0070] In any embodiment, the solvents in the acidic solution and the silver sulfate dispersion are selected from water or an organic solvent; and the pH of the acidic solution and the silver sulfate dispersion is controlled to be below 2; the present invention adjusts the pH to be below 2 by adding sulfuric acid;
[0071] Preferably, the pH of the acidic solution and the silver sulfate dispersion is below 1;
[0072] See also Figure 1 When the pH is below 1, the solubility of the solution becomes very high, and a uniform metal ion state is formed at the initial stage of nucleation, and the rate of precipitation generally decreases. If the rate of precipitation decreases, the number of crystal nuclei decreases, and the silver particles grow and the crystallinity increases;
[0073]
[0074] In formula (1), V is the rate of precipitate formation, S is the solubility of the precipitate, Q is the amount of precipitated substance present in the solution, and K is a constant;
[0075] According to the above formula, the precipitation generation rate depends on the supersaturation. The greater the supersaturation or the smaller the solubility of the precipitate, the greater the precipitation generation rate. As a result, the number of crystal nuclei increases and the particles become smaller.
[0076] The invention improves the solubility of silver sulfate by controlling the acidity of the acidic solution, slows down the precipitation generation speed, reduces the crystal nucleus, promotes the subsequent particle growth, and generates high-crystallinity silver particles.
[0077] In a second aspect, the present invention provides a silver crystal powder prepared by the above-mentioned method.
[0078] In any embodiment, the intensity ratio of the silver crystal in the (111) and (200) directions is I (111) / I (200) Greater than 4.
[0079] In a third aspect, the present invention provides a silver paste comprising silver crystal powder prepared by the method of the first aspect.
[0080] In any embodiment, the silver paste has a porous structure.
[0081] In a fourth aspect, the present invention provides a method for preparing a silver paste, comprising:
[0082] Ethyl cellulose, butyl carbitol acetate and the silver crystal powder prepared by the first aspect of the method or the silver crystal powder provided by the second aspect are mixed, and the viscosity is adjusted to obtain a silver paste.
[0083] In any embodiment, the mass proportions of the silver crystal powder, ethyl cellulose and butyl carbitol acetate in the silver paste are 70-90wt%, 1-10wt% and 9-20wt%, respectively.
[0084] The present invention is described below by means of specific examples.
[0085] Unless otherwise specified, the reagents used in the embodiments and comparative examples of the present invention are purchased conventionally, and there are no special requirements for the manufacturer and model; and the preparation methods of the acidic solutions of the protective agents in the following embodiments and comparative examples are all prepared by conventional methods, specifically, the protective agent is added to the solvent, the pH of the solution is measured, and then the pH value of the solution is adjusted by using 70% by mass sulfuric acid so that the pH meets the set requirements; the pH value of the silver sulfate dispersion is also adjusted by using 70% by mass sulfuric acid so that the pH meets the set requirements.
[0086] Example 1
[0087] This example provides an example of the preparation of silver crystal powder:
[0088] Add 0.05 mol / dm 3A dispersion of silver sulfate (pH 1) and ascorbic acid were added so that the molar ratio of ascorbic acid to silver sulfate was 1 and the mass ratio of silver sulfate to protective agent was 0.05, and the mixture was stirred and mixed at 500 rpm for 1 hour at 50°C. A 48% sodium hydroxide aqueous solution was added, and the mixture was washed at 80°C for 2 hours, and then ammonium nitrate was added for neutralization. The supernatant was removed from the powder precipitated by natural sedimentation by decantation, and the solvent was replaced with acetone, and the mixture was dried at 35°C for 1 day to obtain a silver crystal powder.
[0089] Comparative Example 1
[0090] This comparative example provides an example of the preparation of silver crystal powder:
[0091] Add 0.05 mol / dm 3 A dispersion of silver nitrate (pH 1) and ascorbic acid were added so that the molar ratio of ascorbic acid to silver nitrate was 1, and the mass ratio of silver sulfate to protective agent was 0.05, and the mixture was stirred and mixed at 500 rpm for 1 hour at 50°C. A 48% sodium hydroxide aqueous solution was added, and after washing at 80°C for 2 hours, ammonium nitrate was added for neutralization. After the supernatant was removed from the powder precipitated by natural sedimentation by decantation, the solvent was replaced with acetone, and the mixture was dried at 35°C for 1 day to obtain a silver crystal powder.
[0092] Figure 2 is a SEM image of the silver crystal powder prepared in Example 1. Figure 2 It can be seen that the silver powder prepared in this embodiment is spherical and the dispersion state is monodisperse;
[0093] Figure 3 Example 1 is a particle size distribution of silver powder measured by a laser diffraction particle size distribution meter. The volume-based median particle size (D50) is 610 nm.
[0094] Figure 5 The X-ray diffraction patterns of silver crystal powder measured by powder X-ray diffraction in Example 1 and Comparative Example 1 are shown in Figure 1. (a) is the X-ray diffraction pattern of silver powder obtained from sulfate in Example 1, and (b) is the X-ray diffraction pattern of silver powder obtained from silver nitrate in Comparative Example 1. Figure 5 It can be seen that, under the same other conditions, using silver sulfate as the silver source, the intensity ratio of (111) to (200) is (111) / I (200) is 4.19; using silver nitrate as the silver source, the intensity ratio of (111) and (200) directions is I (111) / I (200) is 3.87; therefore, the silver powder obtained when silver sulfate is used as the silver source has a higher crystal orientation.
[0095] Figure 6(a) and (b) are the differential thermal curves (DTA) and thermogravimetric curves (TG) of the silver crystal powders in Example 1 and Comparative Example 1 respectively measured by a differential thermogravimetric analyzer. According to DTA, there are exothermic peaks at 320°C in (a) and 260°C in (b) accompanied by a decrease in TG. This indicates that the silver crystal powder prepared using silver sulfate as a raw material has better heat resistance.
[0096] Example 2
[0097] This example provides an example of the preparation of silver crystal powder:
[0098] Add 0.01 mol / dm 3 A dispersion of silver sulfate (pH 1.8) and hydrazine were added, and the molar ratio of ascorbic acid to silver sulfate was 0.5, and the mass ratio of silver sulfate to propyl cellulose was 0.01, and the mixture was stirred and mixed at 700 rpm at 30°C for 5 hours. A 48% sodium hydroxide aqueous solution was added, and the mixture was washed at 80°C for 2 hours, and then ammonium nitrate was added for neutralization. The supernatant was removed from the powder precipitated by natural sedimentation by decantation, and the solvent was replaced with acetone, and the mixture was dried at 35°C for 1 day to obtain a silver crystal powder.
[0099] After testing, the silver crystal powder I obtained in this embodiment (111) / I (200) is 4.01;
[0100] Example 3
[0101] This example provides an example of the preparation of silver crystal powder:
[0102] Add 1 mol / dm 3 A dispersion of silver sulfate (pH 2.0) and hydroquinone were added so that the molar ratio of ascorbic acid to silver sulfate was 2 and the mass ratio of silver sulfate to polyvinyl pyrrolidone was 0.2, and the mixture was stirred and mixed at 800 rpm for 2 hours at 80°C. A 48% aqueous sodium hydroxide solution was added, and after washing at 80°C for 2 hours, ammonium nitrate was added for neutralization. After the supernatant was removed from the powder precipitated by natural sedimentation by decantation, the solvent was replaced with acetone, and the mixture was dried at 35°C for 1 day to obtain a silver crystal powder.
[0103] After testing, the silver crystal powder I obtained in this embodiment (111) / I (200) is 4.05.
[0104] Example 4 and Comparative Example 2
[0105] This embodiment provides an example of preparing silver paste:
[0106] Silver crystal powder, ethyl cellulose and butyl carbitol acetate were mixed in a weight ratio of 85wt%:2wt%:13wt%, and the viscosity of the paste was adjusted to about 200Pa·s to obtain a silver paste, which was coated on a PET film with a film thickness of about 250μm using a scraper, and then dried at 100°C for 2 hours. The silver crystal powder in Example 4 used the silver crystal powder prepared in Example 1, and the silver crystal powder in Comparative Example 2 used the silver crystal powder prepared in Comparative Example 1.
[0107] Figure 7 (a) and (b) are the shrinkage curves of the silver paste in Example 4 and Comparative Example 2 measured by a thermomechanical analyzer (TMA). The test results show that the shrinkage rate of (a) at 600°C is 6%, and the shrinkage rate of (b) is 15%, indicating that the strength ratio is 1. (111) / I (200) Silver crystal powder with an orientation of 4 or more has better heat resistance, which also shows that the technical solution of the present invention improves the shrinkage characteristics of existing silver crystal powder.
[0108] Figure 8 It is the specific resistance value of the sintered body obtained by sintering the silver paste of Example 4 of the present invention at 400°C to 900°C for 10 minutes. Figure 8 The specific resistance value of the silver paste of Example 4 at 400°C is 4.16×10 -6 (·cm), while the specific resistance at 900°C decreased to 2.3×10 -6 This indicates that the silver paste prepared in Example 4 has good thermal stability and excellent high-temperature electrical conductivity.
[0109] In addition, the results of SEM observation of the surfaces of the sintered bodies obtained by sintering the silver pastes obtained in Example 4 and Comparative Example 2 at 900° C. for 10 minutes are shown in FIG. Fig. 9 (a) and (b). Fig. 9 (a) shows that the silver paste sintered body of Example 4 has many pores and is a porous body; Fig. 9 (b) shows that the sintered body of the silver paste of Comparative Example 2 has a dense structure, which indicates that the porous body of the silver paste prepared by the method of the present invention improves the adhesion with the ceramic substrate and exhibits the characteristic of being difficult to produce cracks.
[0110] Embodiment 5-6
[0111] Silver crystal powder, ethyl cellulose and butyl carbitol acetate were mixed in a weight ratio of 73wt%:6wt%:11wt%, and the viscosity of the paste was adjusted to about 200Pa·s to obtain a silver paste, which was applied on a PET film with a film thickness of about 250μm using a scraper, and then dried at 100°C for 2 hours. The silver crystal powder in Example 5 used the silver crystal powder prepared in Example 2, and the silver crystal powder in Example 6 used the silver crystal powder prepared in Example 3.
[0112] The silver pastes prepared in Examples 5 and 6 also have a porous structure after sintering at 900°C. The properties of the silver pastes obtained in Examples 5 and 6 were tested, and the specific resistance values at 400°C were 4.3×10 -6 W·cm and 4.4×10 - 6 W·cm, and the specific resistance value at 900℃ is 2.4×10 -6 W·cm, the shrinkage curve of the silver paste was measured by a thermomechanical analyzer (TMA), and the test results showed that the shrinkage rates of the silver pastes in Examples 5 and 6 at 600° C. were both about 6%.
[0113] In summary, the silver nanoparticles prepared by the method of the present invention have uniform particle size and good thermal shrinkage and crystallization properties. The silver paste prepared using the method has a porous structure and has good electrical conductivity and heat resistance, and has good application prospects.
[0114] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing silver crystal powder, characterized in that: include: Silver sulfate and a reducing agent are added to the acidic solution of the protective agent, and a reduction reaction is carried out under heating and stirring conditions to obtain silver crystal powder.
2. The method for preparing silver crystal powder according to claim 1, characterized in that: The protective agent is at least one of gum arabic, propyl cellulose, ethyl cellulose and polyvinyl pyrrolidone.
3. The method for preparing silver crystal powder according to claim 1, characterized in that: The reducing agent is selected from at least one of ascorbic acid, hydrazine, hydroquinone, phenylhydrazine and formalin.
4. The method for preparing silver crystal powder according to claim 1, characterized in that: The heating temperature is 30-80°C, and the reaction time is 5-1h.
5. The method for preparing silver crystal powder according to claim 1, characterized in that: Silver sulfate was added in the form of a silver sulfate dispersion, and the concentration of the added silver sulfate dispersion was 0.01 mol / dm 3 -1mol / dm 3 .
6. The method for preparing silver crystal powder according to claim 1, characterized in that: The concentration of the protective agent in the acidic solution of the protective agent is 1 g / L-20 g / L.
7. The method for preparing silver crystal powder according to claim 1, characterized in that: The solvent of the acidic solution and the solvent of the silver sulfate dispersion are both selected from one of water and an organic solvent, and the organic solvent does not contain a hydroxyl group.
8. The method for preparing silver crystal powder according to claim 1, characterized in that: The pH of the acidic solution is below 2.
9. The method for preparing silver crystal powder according to claim 8, characterized in that: The pH of the solution was adjusted to below 2 by adding sulfuric acid.
10. A silver crystal powder, characterized in that: Prepared by the method according to any one of claims 1 to 9.
11. The silver crystal powder according to claim 10, characterized in that The intensity ratio of the silver crystal in the (1 11) and (2 0 0) directions is I (111) / I (200) Greater than 4.
12. A silver paste, characterized in that: The invention relates to a silver crystal powder prepared by the method according to any one of claims 1 to 9.
13. The silver paste according to claim 12, characterized in that: The silver paste has a porous structure after sintering.
14. A method for preparing a silver paste, characterized in that: include: Ethyl cellulose, butyl carbitol acetate and silver crystal powder prepared by any one of claims 1 to 9 are mixed, and the viscosity is adjusted to obtain a silver paste.
15. The silver paste according to claim 12, characterized in that: Apply to the electrode surface.
Citation Information
Patent Citations
Grain-size-controllable high dispersion type spherical ultrathin silver powder preparing method
CN111331150A
Preparation method of nano silver with controllable particle size
CN111992734A
Micron-sized spherical silver powder as well as preparation method and application thereof
CN112589113A
Full-nano twin-crystal structure silver deposition layer with high {111} preferred orientation and preparation method of full-nano twin-crystal structure silver deposition layer
CN116334703A
Flaky micron silver powder and preparation method thereof
CN117300149A